A rapid increase of large-sized waterfowl does not explain the population declines of small-sized waterbird at their breeding sites - Holopainen Sari; Čehovská Markéta; Jaatinen Kim; Laaksonen Toni; Lindén Andreas; Nummi Petri; Piha Markus; Pöysä Hannu; Toivanen Tero; Väänänen Veli-Matti; Lehikoinen Aleksi (ELSEVIER, 2025)
Certain species experience rapid population increases in human-modified and -affected environments. Conservation actions and increased wintertime food availability have led to a population increase of several large herbivorous waterbird species. In Northern Europe, this trend is opposite to the overall decrease of several smaller waterbird species. We examined whether the recovery of a flagship species, the whooper swan (Cygnus cygnus), and the spreading of the nonnative Canada goose (Branta canadensis), cause asymmetric competition with other sympatric waterbirds at their breeding sites. We used data from the national Finnish waterbird surveys collected in the late 1980s and early 2020 s at 942 sites, to assess the site-level effects of large herbivore occurrence on other waterbird species, while considering their trophic overlap. We hypothesised that there could be competitive effects of large herbivorous on smaller species, especially those with similar foraging niches. We however found that other waterbird populations have decreased less at sites occupied by whooper swans since the 1980 s. Canada goose site occupation was not associated with the abundance of other waterbirds. Thereby, our findings are not consistent with the suggestion that population increases of large herbivore species lead to asymmetric competition on the breeding wetlands. The whooper swan may potentially act as an indicator of habitat quality and further on as a flagship umbrella species with multidisciplinary conservation benefits, of which may accrue benefits also to other waterbirds exhibiting declining population trends. Our findings underline the importance of considering species interactions when designing and implementing management actions in conservation strategies.